2014
DOI: 10.1097/qai.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

Increased Arterial Inflammation Relates to High-Risk Coronary Plaque Morphology in HIV-Infected Patients

Abstract: Background Mechanisms predisposing HIV-infected patients to increased CVD risk remain unclear. Objective To determine the interrelationship between arterial inflammation and high-risk coronary plaque morphology in HIV-infected patients with subclinical coronary atherosclerosis. Methods 41 HIV-infected patients on stable ART without known CVD but with atherosclerotic plaque on coronary CT angiography were evaluated with 18F-FDG-PET. Patients were stratified into two groups based on relative degree of arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 14 publications
1
60
1
Order By: Relevance
“…Among PLWHIV, data using CT have shown that there is a marked increase in the prevalence of both non-calcified plaque 32 and HRP in coronary arteries of PLWHIV 8, 33 . For example, Post et al, showed in a study of 618 PLWHIV that the prevalence of any non-calcified coronary plaque was 63% as compared to 53% in uninfected controls 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Among PLWHIV, data using CT have shown that there is a marked increase in the prevalence of both non-calcified plaque 32 and HRP in coronary arteries of PLWHIV 8, 33 . For example, Post et al, showed in a study of 618 PLWHIV that the prevalence of any non-calcified coronary plaque was 63% as compared to 53% in uninfected controls 21 .…”
Section: Discussionmentioning
confidence: 99%
“…One such study showed that the atherosclerotic inflammation correlates with markers of monocyte activation. Subsequent studies showed an association between arterial inflammation and structural measures of coronary atherosclerosis, including the presence of high-risk morphological features 14 . Further, among HIV-infected individuals, immune activation and chronic inflammation persist and are thought to lead to collagen deposition and fibrosis of lymphoid tissue; 15 as fibrosis has been reported in other organs such as the liver 16 as well as the myocardium.…”
mentioning
confidence: 99%
“…Furthermore, we observed that the degree of arterial inflammation in HIV correlates with markers of monocyte activation, 7 and in a separate study, we observed that extra-coronary arterial inflammation correlates with the presence of high-risk coronary plaques. 37 Hsue et al recently extended those findings, and observed that the tissue measures on FDG accumulation relate to markers of viral persistence in HIV. 38 Hence a substantial literature has emerged in HIV-positive individuals, which links immune activation to arterial inflammation.…”
Section: See Related Article Pp 372-380mentioning
confidence: 78%